2018
DOI: 10.31219/osf.io/pjhrq
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Awesome play: Awe increases preschooler’s exploration and discovery

Abstract: Affective states, exploration, and learning are tightly inter- twined. For example, research has connected surprise to play and learning in early development (Stahl & Feigenson, 2015), but less is known about the potential impact of other affec- tive states and how they might influence exploration and sub- sequent discovery. Given that past research has suggested that awe may increase feelings of uncertainty and lead to pursuit of cognitive accommodation in adults (Valdesolo & Graham, 2014), we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Finally, it is an open question how explore-exploit behavior relates to emotions such as curiosity, interest, and affect [92,93,94,95,96,97]. While these concepts are thought to inspire or inhibit exploration or exploitation, the relationship between them and exploreexploit behavior has not been sufficiently explored.…”
Section: How Does Explore-exploit Behavior Relate To Other Constructs?mentioning
confidence: 99%
“…Finally, it is an open question how explore-exploit behavior relates to emotions such as curiosity, interest, and affect [92,93,94,95,96,97]. While these concepts are thought to inspire or inhibit exploration or exploitation, the relationship between them and exploreexploit behavior has not been sufficiently explored.…”
Section: How Does Explore-exploit Behavior Relate To Other Constructs?mentioning
confidence: 99%
“…For example, in the pharmaceutical sciences, researchers attempt to find new methods to produce vaccines even faster in the future. Children at play might also exhibit this kind of intrinsic drive to explore actions that train them to explore even more actions 9,19 . Empowerment differs from uncertainty-guided strategies, in that it focuses less on reducing uncertainty about the environment and more on the intrinsic drive towards a state of maximum influence 20 .…”
Section: Exploration As Empowermentmentioning
confidence: 99%
“…It has been proposed that uncertainty elicited by this contrast provokes a need for accommodation, ultimately triggering a drive to extend and/or change existing knowledge structures (Keltner and Haidt, 2003). In support of this, in one study, preschool children who were shown awe-inducing videos reported a smaller perceived self-size, and subsequently heightened exploration relative to children shown happy-or calm-inducing videos (Colantonio and Bonawitz, 2018). Thus, it is possible that infants whose caregivers engage in awe-inducing activities tend to be more sensitive to gaps in their knowledge, which may, in turn, lead them to show greater looking preferences for physically impossible events.…”
Section: The Relation Between Parenting Practices and Infant Curiositymentioning
confidence: 96%
“…We also asked about children's exposure to awe-inducing experiences, as recent experimental work has linked the experience of awe to epistemic curiosity (Anderson et al, 2020;Paulson et al, 2021), and has even shown a causal link between exposure to awe and curiosity (Colantonio and Bonawitz, 2018). We selected awe-inducing experiences that past work has linked to curiosity, such as going to science or art museums (Gottfried et al, 2016) and spending time in nature (Keltner and Haidt, 2003;Valdesolo and Graham, 2014).…”
Section: The Multidimensionality Of Curiositymentioning
confidence: 99%
See 1 more Smart Citation